Spirituality and low-risk consumption of alcohol in young adults - Díaz Heredia, Luz Patricia; Muñoz S, Alba Idaly (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> The relationship between spirituality and health, as well as it effect on adopting healthy behaviors, is a topic of interest for nursing and, in general, for social and life sciences. Spirituality, as a human realm, is a relevant research theme that is often related to the promotion of health in individuals. Studies indicate that spirituality is related to mental and physical health, being a protective and promoting factor of healthy behaviors, among them low-risk consumption of alcohol in young adults. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->